2015
DOI: 10.1177/1469540515586870
|View full text |Cite
|
Sign up to set email alerts
|

Musical preferences and technologies: Contemporary material and symbolic distinctions criticized

Abstract: Music as a mechanism for social distinction is well established. Yet, perhaps more than any other form of cultural expression, it is music which has been systematically transformed by emerging technologies. From the gramophone, radio, cassette and CD, through to portable devices and shared through social media, music is in constant flux. To separate taste for music from its various acquisitional forms is to undermine its role in society. In this article, our aim is to integrate within taste and cultural consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 65 publications
0
24
0
6
Order By: Relevance
“…The full list of activities is shown in Table A1 (see online appendix). Our analytical strategy involves MFA, which is a development of MCA (Leguina et al, 2015;Pagès, 2015). MCA is the method used by Bourdieu in Distinction (Bourdieu, 1984) for creating a multidimensional spatial representation of the relationship between variables -that is, in contrast to their reduction into dependent-independent "causal" hierarchies by conventional multivariate techniques.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full list of activities is shown in Table A1 (see online appendix). Our analytical strategy involves MFA, which is a development of MCA (Leguina et al, 2015;Pagès, 2015). MCA is the method used by Bourdieu in Distinction (Bourdieu, 1984) for creating a multidimensional spatial representation of the relationship between variables -that is, in contrast to their reduction into dependent-independent "causal" hierarchies by conventional multivariate techniques.…”
Section: Methodsmentioning
confidence: 99%
“…Here the choice of analytical approach is crucial because the way in which the particular set of participation indicators available in a dataset such as the TPS is mobilised will shape the contours of the cultural field it describes. Our solution to this issue is to apply a technique called Multiple Factor Analysis (MFA) (Leguina, Arancibia-Carvajal, & Widdop, 2015;Pagès, 2015). MFA builds on Multiple Correspondence Analysis (MCA), which is a form of geometric data analysis designed to explore and represent relationships among many categorical variables that is particularly associated with the school of cultural analysis established by Pierre Bourdieu (Le Roux & Rouanet, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, theorizing digitization in cultural consumption from the perspective of individual decision-making leads to results that are largely in line with other studies. Also Leguina et al (2017) and Mihelj et al (2019) found that digital media do not attenuate but rather reinforce social inequalities in cultural consumption. Note, however, that these studies are more of exploratory character while the present one is more explanatory.…”
Section: Main Findingsmentioning
confidence: 99%
“…The most notable example of this is the 'poprockization' of music throughout the world: the growing influence of American and British pop-rock music and its local adaptations, which is conceptualized as 'expressive isomorphism' standardizing national peculiarities in world culture (Regev, 2013;Varriale, 2016). Finally, technological changes, especially digitalization, may play a role in the increase of cultural heterogeneity, as the proliferation of distributable and portable cultural forms and their easy consumption -distinct from traditionally ceremonial methods of consuming highbrow culture such as visiting concerts or museums -are clearly factors behind the present 'cultural abundance' (Wright, 2011(Wright, , 2015Leguina, Arancibia-Carvajal and Widdop, 2017).…”
Section: The Opening Up Of Legitimate Culture: Theoretical Perspectivesmentioning
confidence: 99%